Changes in functional structure of aquatic insect communities across environmental gradients in mountain streams - Gutierrez, Carolina, author; Poff, N. LeRoy, advisor; Ghalambor, Cameron, advisor; Neuwald, Jennifer, committee member; Webb, Colleen, committee member (Colorado State University. Libraries, 2024)
This study investigates the functional diversity of aquatic insect communities across environmental gradients within Rocky Mountain headwater streams, aiming to better understand how elevation, water temperature, and canopy cover shape the structure and dynamics of these communities. Functional diversity (FD) is defined here as the range, distribution, and relative abundance of organismal traits, which together provide deeper insight into ecosystem functionality than species diversity alone. FD was quantified through three primary metrics: functional richness (FRic), functional evenness (FEve), and functional divergence (FDiv), each capturing distinct aspects of how species contribute to ecosystem functioning. This multidimensional approach enables a nuanced examination of how aquatic insect communities respond to various environmental stressors and spatial constraints, particularly as altitudinal changes present unique challenges in terms of temperature variability and resource availability. Field data were collected from twenty-four stream sites distributed across elevation bands ranging from 1,500 to 3,500 meters. Sites were replicated in three different drainage systems to account for regional variation, with insect specimens collected and assessed for twenty functional traits. These traits included parameters such as voltinism (number of life cycles per year), adult lifespan, emergence synchronization, and dispersal ability, all of which are critical in determining an insect's role in the ecosystem. Canopy cover and water temperature were also measured to evaluate how localized microclimates and light availability influenced community composition. Results revealed a significant decline in functional richness with increasing elevation, with the steepest reductions observed in streams with sparse canopy cover. Functional richness was highest in areas where canopy cover ranged between 65-78%, and water temperature was between 8°C and 15°C, suggesting that moderate canopy cover and specific thermal conditions support more functionally diverse communities. Functional evenness and divergence, while showing less pronounced patterns, indicated that the most extreme trait values are critical for resilience in these systems, particularly under fluctuating environmental conditions. Trophic interactions further illustrate the importance of specific functional groups, such as predators, grazers, and filterers, in shaping community structure. The analysis of beta diversity demonstrated substantial turnover in functional traits across elevation gradients, emphasizing the heterogeneity of insect communities within low-order, high-altitude streams and reinforcing the role of environmental filtering in community assembly. These findings highlight the vulnerability of headwater stream ecosystems to environmental changes and underscore the importance of functional diversity metrics in ecological monitoring and conservation efforts. Overall, this study contributes to our understanding of how functional environmental gradients structure diversity and provides a foundation for comparative studies on functional diversity in tropical versus temperate mountain stream ecosystems, particularly in the context of global biodiversity conservation.
Keywords: EVOTRAC; functional diversity; mountain streams; food webs; aquatic insects; functional structure